RISIKO HIPERTENSI KARENA KEHILANGAN GIGI PADA LANSIA - Rasmidar Samad (DiscoverSys Inc., 2002)
Changing dietary patterns in elderly as a result ofchange in dental status, such as a loss of teeth anddenture wearing they are may cause reductions of someessential foods and may be cause various healthdisorders. The purpose of this study was to investigate thecorrelation between loss of teeth, denture wearing andhypertension and they are relative risk. Study design is across sectional (n = 131 elderly). We performed a linermultiple regression to analysis between loss of teeth,wearing denture and hypertension (CI: 95%) Result: onehundred thirty-one sample were recruited. Mean age63,37in institutional elderly 62,2% and 64% non institutionalwaslossofposteriorteeth.Theysuggested have a correlation between loss of teethR2 : 0.31 (p:0.043), wearing denture (p. 0.000, RR. 1.72,CI 95%) . and hypertension.